1997
DOI: 10.1038/sj.onc.1201215
|View full text |Cite
|
Sign up to set email alerts
|

p53 associates with trk tyrosine kinase

Abstract: The p53 tumor suppressor gene encodes a phosphoprotein which when overexpressed can induce growth arrest at the G1 and G2/M phases of the cell cycle, promote di erentiation and apoptosis. This paper demonstrates that p53 can associate with trk tyrosine kinase. Expression of a murine temperature-sensitive (ts) p53 mutant in PC12 cells overexpressing trk (a model system to analyse cellular di erentiation and signal transduction induced by NGF) induces morphological changes in the absence of NGF stimulation at 32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
28
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 42 publications
5
28
1
Order By: Relevance
“…Cell extracts of NGF stimulated NIHtrk+tsp53-2 grown at 328C, NIH3T3 and p53 negative cells (p53 7/7 ) were immunoprecipitated with either anti-trk A B-3 or PAb 248 antibodies. Immunoblotting analysis with anti-trk 203 antibodies showed that PAb 248 was able to coprecipitate trk A associated with p53 and when comparing total to bound trk A, 25 ± 30% of the trk A from cell extracts associated with p53 in agreement with previous results (Montano, 1997). PAb 248 did not appear to non-speci®cally recognize any other protein(s) (Figure 1c).…”
supporting
confidence: 90%
See 4 more Smart Citations
“…Cell extracts of NGF stimulated NIHtrk+tsp53-2 grown at 328C, NIH3T3 and p53 negative cells (p53 7/7 ) were immunoprecipitated with either anti-trk A B-3 or PAb 248 antibodies. Immunoblotting analysis with anti-trk 203 antibodies showed that PAb 248 was able to coprecipitate trk A associated with p53 and when comparing total to bound trk A, 25 ± 30% of the trk A from cell extracts associated with p53 in agreement with previous results (Montano, 1997). PAb 248 did not appear to non-speci®cally recognize any other protein(s) (Figure 1c).…”
supporting
confidence: 90%
“…The same result was obtained after prolonged exposures. Also, when cell extracts of p53 7/7 cells transfected with trk A (p53 7/7 trk A) were immunoprecipitated with PAb 248; immunoblotting analysis with anti-trk A 203 antibodies showed that PAb 248 did not immunoprecipitate trk A in agreement with previous data (Montano, 1997). Therefore, these results show that PAb 248 and anti-abl ab-3 only recognize p53 and cabl respectively.…”
supporting
confidence: 89%
See 3 more Smart Citations